FAKTOR YANG MEMPENGARUHI BIOSINTESIS IAA OLEH AZOSPIRILLUM - Danapriatna, Nana (Majalah Ilmiah SOLUSI, 2015)
Auxin is a growth hormone that can be produced by bacteria, including Azospirillum. Pyruvate indole 3 acetic acid (IAA) is one form of auxin which can be produced by Azospirillum. The main precursor in the formation of IAA by Azospirilum is tryptophan. IAA biosynthesis by Azospirillum consists of the major pathway Indole 3 pyruvate and minor pathway through Tryptamine. Production of IAA by Azospirilum influenced by genetic factors and environmental factors. Genes involved in the production process of IAA by Azospirillum is ipdC gene that determines the formation of pyruvate decarboxylase enzyme indole 3. Environmental factors that influence the IAA biosynthesis is the availability of carbon, medium pH, oxygen and nitrogen. Production of IAA by Azospirillum increased under conditions of limited availability of carbon and low pH of medium. Provision of nitrogen can increase the production of IAA. Aerobic environmental conditions resulted in the production of IAA by Azospirillum be lower compared to anaerobic conditions (oxygen limited). This paper describes the biosynthesis of IAA by Azospirillum through pathways involving tryptophan as the precursor and the factors that influence it. Key Words : Azospirilum, IAA, Tryptophan, Indole-3-pyruvate, Tryptamine